A study of neonatal hyperbilirubinemia from a tertiary care hospital in Northern India - Bedi, Nidhi; Kumar, Chandra Mohan; Singh, Shweta (Indian Journal of Child Health, 2018)
Objective: The objective of this study was to analyze the incidence of pathological jaundice, average time of presentation, mean duration of phototherapy, and need for exchange transfusion with appropriate medical management. Methods: Thus, retrospective study was conducted at neonatal intensive care unit of a tertiary care hospital from August 2017 to August 2018. All live births who were diagnosed with neonatal hyperbilirubinemia and requiring treatment were included in the study. Exclusion criteria included any baby with conjugated serum bilirubin >20% of total serum bilirubin or >2 mg/dl or neonate with any congenital malformation. Results: Nearly 5% of total babies delivered developed neonatal jaundice requiring treatment. The most common causes isolated were ABO incompatibility followed by Rh incompatibility. Almost 46% of babies were not found to have any cause. The most likely etiology concluded in this group was breastfeeding jaundice. Conclusion: Breastfeeding jaundice should be considered as one of the common causes of pathological jaundice making lactational counseling during antenatal and postnatal period an essential component of management and prevention of pathological jaundice. Early detection and timely intervention with lesser invasive treatment modalities such as intravenous immunoglobulin G, hydration, and phototherapy should be attempted aggressively to avoid need for high-risk procedures like exchange transfusion.